ROOT SQUARE MEAN LABELING OF ARROW GRAPHS WITH ENCODING AND DECODING - Christy, T; Palani, G (TWMS journal of applied and engineering mathematics, 2025)
A graph G with p vertices and q edges is called a Root Square mean labeling if it is possible to label the vertices x [member of] v with distinct labels p(x) from 1, 2, ***, q + 1 in such a way that each edge e = ab is labeled with [Please download the PDF to view the mathematical expression] then the edge labels are distinct. In this case p is called Root Square mean(RSM) labeling of G. In this paper we prove Arrow graphs [A.sup.2.sub.n],[A.sup.2.sub.n],[A.sup.2.sub.n] admits Root Square mean (RSM) labeling.In today's world, digital data transfer is becoming more and more common in all industries. Data security plays a critical role in the delivery and storage of data. Labeling is an essential component of the cryptosystem. A new approach in the encoding and decoding process on the Root Square Mean Labeling is applied in this paper through an algorithm for encoding and decoding of secured message. Keywords: Root Square mean (RSM) labeling, Arrow graphs AMS Subject Classification:05078